The Effect of Using Rolling Quiz Box Media to Improve the Critical Thinking Ability of Grade 3 Students at Madrasah Ibtidaiyah - Cindy Novita Sari; Rora Rizky Wandini (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2023)
This research aims to determine the effect of using Rolling Quiz Box media to improve students' critical thinking skills. The method in this research uses quantitative research of the Quasi Experiment type with a One Group Pretest-Posttest design. In this design there are two study groups, namely the control class and the experimental class. At the beginning of the research, a pretest was given to see the students' initial understanding and a posttest was given after the treatment for the control class teaching without media and the experimental class teaching using Rolling Quiz Box media. The population and sample in this study were class III MIN 1 students in Medan City. From the results of data analysis, it can be concluded that the use of Rolling Quiz Box media, education which influences students' critical thinking skills, has proven to be beneficial. This study shows a significant increase in academic performance, as evidenced by a fairly large increase in the posttest average of the control group to 64.79 and the experimental group, namely 81.67.